Zoonimy Księgi Kapłańskiej (studium porównawcze na macedońskich przekładach) - Dimitrieva, Branka (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2014)
The aim of the work is a comparative analysis of zoonyms (animal names) used in the 11th part of Leviticus. The starting point of the comparative analysis is the Macedonian language and the most commonly used translations of the Bible into that language.
Keywords: Old Testament; Leviticus; Macedonian language; South Slavic languages; zoonyms